Pengaruh Dosis Dan Waktu Aplikasi Poc Ampas Kopi Terhadap Pertumbuhan Benih Tebu Bud Set Varietas Cening - Pramana, Waskitha Budi; Hartini, Hartini (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2021)
This study aims to determine the dose and time of application of the best coffee dregs Liquid Organic Fertilizer (POC) for sugarcane seedlings (Saccharum officinarum L.) cening variety bud set. The sugarcane seeds used are obtained from PG. Lestari, Patianrowo, Nganjuk, East Java. The study was compiled using a randomized block design (RBD) with 2 treatment factors. The first factor is the POC dosage of coffee dregss with treatment variations P0 without fertilizer application, P1 with a dose of 10ml / liter of water, P2 30ml / liter of water, and P3 50ml / liter of water. The second factor is application time with 3 variations of treatment, namely M1 POC applied to sugarcane 1-3-5 weeks after planting (MST), M2 at sugarcane age 2-4-6 MST, and M3 at sugarcane 3-5-7 MST age. Data analysis used variance (ANOVA) with a significant 5%, if there is a significant difference, continue with the Duncan Multiple Range Test (DMRT). The results showed that the interaction between dose treatment and application time of coffee dregs POC had no significant effect on plant height, number of leaves, stem diameter, root length, wet weight and dry weight. Different dosage treatments had a significant effect on plant height, number of leaves, root length, wet weight and dry weight. Different application time treatments had a significant effect on plant height, wet weight and dry weight. The best dosage for coffee dregs POC for sugarcane is 30 ml / liter of water. The best application time for coffee dregs POC is at the age of 3-5-7 MST sugarcane.